Umbilical Cord Hepcidin Concentrations Are Positively Associated with the Variance in Iron Status among Multiple Birth Neonates. Issue 11 (22nd September 2018) - Ru, Yuan; Pressman, Eva K; Guillet, Ronnie; Katzman, Philip J; Vermeylen, Francoise; O'Brien, Kimberly O
Abstract: Background: Hepcidin is a systemic regulator of iron homeostasis. Little is known about the relative role of maternal compared with cord hepcidin on neonatal iron homeostasis. Objective: This study was undertaken to evaluate inter- and intrauterine variance in neonatal iron status, vitamin B-12, folate, and inflammatory markers in a cohort of twins ( n = 50), triplets ( n = 14), and quadruplets ( n = 1) born to 65 women. Methods: Umbilical cord blood was obtained from 144 neonates born at 34.8 ± 2.7 wk of gestation with a mean birth weight of 2236 ± 551 g (means ± SDs). Cord hemoglobin and cord serum measures of ferritin (SF), soluble transferrin receptor (sTfR), hepcidin, erythropoietin (EPO), iron, vitamin B-12, folate, interleukin 6, and C-reactive protein were evaluated. Results: Intraclass correlation coefficient (ICC) analyses were used to examine inter- and intrauterine variance in neonatal iron indicators. A greater variability in cord hepcidin (ICC = 0.39) was found between siblings. Cord hepcidin had the greatest association with cord iron indicators because cord hepcidin alone captured 63.8%, 48.4%, 44.4%, and 31.3% of the intrauterine variance in cord hemoglobin, SF, sTfR, and EPO, respectively, whereas maternal hepcidin had no effect on cord iron indicators. Significantly greater differences in cord SF ( P = 0.03), sTfR ( P = 0.03), hepcidin ( P = 0.0003), and EPO ( P = 0.03) were found between di- and trichorionic siblings than between monochorionic siblings. In contrast, cord folate (ICC = 0.79) and vitamin B-12 (ICC = 0.74) exhibited a greater variability between unrelated neonates. Conclusions: In summary, fetally derived hepcidin might have more control on intrauterine variance in iron indicators than maternal hepcidin and appears to be capable of regulating fetal iron status independently of maternal hepcidin. The use of a multiple-birth model provides a unique way to identify factors that may contribute to placental nutrient transport and iron stores at birth.